The Effect of Compensation and Digitalization on Employee Performance of PT Pelabuhan Indonesia III (Persero) In Surabaya - Suryani, Olivia Dwi; Liftiana, Rika; Zaman, Komarun (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to determine the effect of compensation and digitalization on employee performance of PT Pelabuhan Indonesia III (Persero) in Surabaya, This type of research uses quantitative research methods. This study involves surveys and secondary data analysis involving employees in the Archives Unit. The results of the study indicate that fair compensation and effective digitalization both contribute significantly to improving employee performance. Adequate compensation serves as the main motivator in increasing job satisfaction, while digitalization speeds up the work process and facilitates access to information. The results of this study indicate that compensation has a positive effect on employee performance and compensation and digitalization have a positive effect on employee performance at PT Pelabuhan Indonesia Regional III (Persero).